2014
DOI: 10.1111/bjh.13048
|View full text |Cite|
|
Sign up to set email alerts
|

Diagnosing and following adult patients with acute myeloid leukaemia in the genomic age

Abstract: The diagnosis and follow-up process of adult patients with acute myeloid leukaemia (AML) is challenging to clinicians and laboratory staff alike. While several sets of recommendations have been published over the years, the development of high throughput screening and characterization for both genetic and epigenetic events have evolved with astonishing speed. Here we attempt to provide a practical guide to diagnose and follow adult AML patients with a focus on how to balance the wealth of information on the on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 109 publications
(108 reference statements)
0
5
0
Order By: Relevance
“…We explored the CD34+CD38‐ stem cell containing subset further in MPN by evaluating aberrant hMICL expression, which has proven useful in defining the malignant stem cells in AML and MDS . Xenograft transplantation studies have shown the CD34+CD38‐hMICL+ subset to hold leukemia initiating potential, and aberrant hMICL expression can be employed in monitoring minimal residual disease in AML . While hMICL+ stem cells were very rare in PV and ET patients and absent in controls, intriguingly, MF stem cells displayed aberrant hMICL expression similar to what has been reported in AML and MDS.…”
Section: Discussionmentioning
confidence: 96%
“…We explored the CD34+CD38‐ stem cell containing subset further in MPN by evaluating aberrant hMICL expression, which has proven useful in defining the malignant stem cells in AML and MDS . Xenograft transplantation studies have shown the CD34+CD38‐hMICL+ subset to hold leukemia initiating potential, and aberrant hMICL expression can be employed in monitoring minimal residual disease in AML . While hMICL+ stem cells were very rare in PV and ET patients and absent in controls, intriguingly, MF stem cells displayed aberrant hMICL expression similar to what has been reported in AML and MDS.…”
Section: Discussionmentioning
confidence: 96%
“…After a period hallmarked by productivity but before WES became mainstream, many researchers and clinical laboratories turned to panel sequencing. The seemingly little new knowledge to be gained by exome sequencing and the difficulties in comprehending the broad data output for the clinicians emphasized the usefulness of offering panel sequencing for diagnostic purposes (Roug et al , ). The focused panels enabled much deeper sequencing, and the overlapping genomic aberrations across disease entities in the lymphoid or myeloid lineages and previous studies made it possible to characterize the genomic profiles and classify patients into molecular or prognostic subgroups, as has been done for MDS (Haferlach et al , ).…”
Section: Sequencing Branched Into the Myeloid Lineagementioning
confidence: 99%
“…6 Moreover, a baseline immunophenotypic result before treatment is important for treatment response evaluation and measurable residual disease (MRD) monitoring. [7][8][9] Cytogenetic and molecular analyses are also required for all newly-diagnosed AML to predict patient prognosis and guide treatment decision. 4 Besides, these genetic data are also used to further classified patients into different subtype according to WHO 2016 classification criteria.…”
Section: The Diagnostic Tool Box In Amlmentioning
confidence: 99%